NARRATING THE NATION IN AMITAV GHOSH’S THE SHADOW LINES - Singh, Vikram; Deep, Aman; Ritu; Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Amitav Ghosh’s The Shadow Lines unfolds a captivating narrative exploring the intricate relationship between borders, identity, and freedom. It displays the profound impact of political boundaries and historical events on personal identities and human lives. This paper sheds light on national identity, the pursuit of freedom, and the cultural transformations that resulted from India’s partition and the rise of East Pakistan through Tha’mma, one of the central characters through the novel’s narrative structure and character development, the profound impact of borders on individual and collective experience is explored. Tha’mma’s story is examined to explore how borders influence one’s sense of place, culture, and identity as she transitions from her family home in Dhaka to Calcutta. It illustrates how borders and boundaries can redefine one’s sense of belonging by looking at Tha’mma’s adaptation to her new surroundings. By emphasizing how geopolitical events can cause individuals to become foreigners in their home countries, The Shadow Lines offers profound insights into the essence of freedom, identity, and the lasting impact of borders on human experience as they relate to personal and familial life after these changes. Through the intricate narratives of Tha’mma, Ila, Jethamoshai, and other characters, the novel lays bare the intricate relationship between personal and national identities. The paper offers a new perspective regarding the transformative legacy of history and politics on individual lives, emphasizing that borders are as much about the mind as they are about the land, giving an in-depth understanding of how boundaries affect perceptions of self and home.